PENDIDIKAN SEKS PADA ANAK USIA DINI DITINJAU DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Tawaduddin Nawafilaty (Universitas Islam Lamongan, 2018)
Introducing sex education in early childhood in the modern era is not such a taboo instead of being forbidden from discussion. Given the widespread sexual abuse and child abuse, this phenomenon should be a concern for all circles. Not only do families and educators participate in addressing the issue but also the wider community has to provide supervision and take account of it. Introducing or givingÂ early childhood understanding about sex that refers to Islamic religious education which is widely discussed by Muslim intellectuals based on such religious sources asÂ theQur'an,Hadith, Ijma and so fourth are part of dealing with the problem of child sexual abuse. On this stand, Sex education is not but such an information about the importance of knowing the name and function of body parts, the understanding of sex differences, the understanding of intimacy or sexual relationship as well as the understanding of the existing values and norms in society related to gender identity and inculcating religious cometment will greatly help children pass through the next stage of age